Evaluation of formation and health risks of disinfection by-products in drinking water supply of Ggaba waterworks, Kampala, Uganda - Annitah, Nshemereirwe; Feleke, Zewge; Enos, Malambala (IWA Publishing, 2022)
In developing countries, the evaluation of disinfection by-products in drinking water has been neglected because most water utility companies focus on microbial elimination. As a result, this study aimed at evaluating trihalomethane formation, the relation between water quality parameters and trihalomethane formation, and the estimation of the associated potential health risks in drinking water. The headspace purge and trap coupled with a gas chromatography–mass spectrometry technique was used to quantify trihalomethane. The concentrations of trihalomethane found in the water were within the National Water and Sewerage Corporation, World Health Organization guidelines, and the United States Environmental Protection Agency standards. Total organic carbon, ultraviolet absorbance at 254 nm, bromide concentration, and the temperature had a positive and significant correlation, pH had a positive but non-significant correlation, while the residual chlorine had a negative but significant correlation with trihalomethane formation. The potential health risk using the WHO index was 0.4, indicating no noncarcinogenic risk to human health in the study area. The lifetime carcinogenic risks of trihalomethane due to oral ingestion, dermal, and inhalation were 2.5×10−5, 9.1×10−6, and 8.3×10−6 for females and 2.4×10−5, 1×10−5, and 7.9×10−6 for males, and the values were within the USEPA acceptable low-risk range of 1×10−6<CR<5.1×10−5. HIGHLIGHTS Disinfection by-products in drinking water are neglected in African water utility companies.; Potential health risks associated with disinfection by-products in drinking water.; The headspace purge and trap coupled with a gas chromatography–mass spectrometry technique was used to quantify trihalomethanes.; The WHO index was 0.4104, indicating no noncarcinogenic risk to human health in the study area.
Keywords: disinfection by-products, drinking water, gas chromatography, trihalomethane